Influence of food availability on demography and local population dynamics in a long-lived seabird. - Oro, Daniel (2004)
Few studies have addressed the effects of food availability as a proximate factor affecting local adult survival in long-lived organisms and their consequences at local population dynamics. We used capture-recapture analysis of resightings of 10 birth cohorts of ringed Audouin's gulls, Larus audouinii, to estimate adult survival and dispersal (both emigration and immigration). For the first time, permanent emigration (the transient effect in capture-recapture analysis) was modelled for the whole population and not only for the newly marked birds. Gulls exploit to a large extent fishes discarded from trawlers, and a trawling moratorium established since 1991 has decreased food supply for the colony. This was used as a natural experiment of food availability to assess its effects on adult survival and emigration. These and other demographic parameters were used in a projection modelling to assess the probabilities of extinction of the colony under two scenarios of lower and higher food availability. Food availability (together with the age of individuals) influenced emigration probabilities, but not adult survival, which was estimated at 0.91 (s.e. = 0.02). When food was in shorter supply during the chick-rearing period, emigration was very high (ca. 65%) for younger breeders, although this rate decreased sharply with age. Probabilities of extinction were very high when food availability was low, and when environmental stochasticity was introduced, and only stochastic immigration from the outside seemed to prevent extinction. The results highlight the importance of dispersal processes in the population dynamics of long-lived organisms.